(untitled) (Oil and Gas Engineering, 2017)
This article provides information about the design of coiled tubing units from different manufacturers that are used in the workover. Shows a typical circuit ground coiled tubing unit and the most complex and criti-cal components and mechanisms that are included in its composition. The main features of the application, as well as the benefits of the technologies used with flush–joint pipe. The major types of repair work carried out by a number more than ten coiled tubing units. It is shown that the technology developed by the authors of the removal of dense sand and clay tubes with abnormally low formation pressure (ALFP). Specified fea-tures to increase economic efficiency in the use of coiled tubing units. Keywords: coiled tubing installation, flush-joint pipe, wells, overhaul, hydraulic machines, tubing.